Under what conditions do venture capital markets emerge - Andrea Schertler (Kiel Institute for World Economics (IfW), 2002)
Venture capital activity differs considerably across countries. Venture capital markets are highly developed in few countries, while these markets are almost nonexistent in many other countries. This paper examines the conditions that have to be fulfilled for liquid venture capital markets to emerge. Using a general equilibrium model, two necessary conditions are identified. First, value added by venture capitalists' active involvement must be high compared to the costs of management support. Second, the number of high-technology enterprises demanding venture capital must exceed a critical level. The paper discusses how differences in financial and innovation systems affect these two conditions.
Keywords: G24; O16; O41; 330; Management support; high-technology enterprises; venture capital finance; Risikokapital; Marktintegration; Internationaler Finanzmarkt; Allgemeines Gleichgewicht; Unternehmensberatung; Hochtechnologiesektor; Break-Even